Myxoid Type of Malignant Fibrous Histiocytoma of the Maxillary Sinus: A Case Report - Amir Hossein Jafarian (Iranian Journal of Otorhinolaryngology, 2011)
Introduction: Myxofibrosarcoma was originally described as the myxoid variant of Malignant Fibrous Histiocytoma (MFH), a high-grade and aggressive sarcoma, which is very uncommon in the head and neck region, with about 100 cases reported up to now. MFH occurring in the maxillary sinus is so rare that only 23 cases have been reported. We hereby report a case of myxofibrosarcoma in the maxillary sinus. Case Report: The case was a 54-year-old male with symptoms of toothache in the right posterior maxillary teeth, a swelling adjacent to maxillary molar region and symptoms of chronic maxillary sinusitis. In clinical examination, the teeth were sensitive to percussion and palpation, but no caries and restoration was detected on his molar teeth. He was suffering from local pain and tenderness over his midface and mild fever, fatigue and some nonspecific vague pain. CT scan showed a mass lesion involving right nasal cavity, maxillary and ethmoidal sinuses. A low-grade malignancy arising from the right maxillary sinus was highly suspected. A surgery was done to remove the mass. The histological and immunohistochemical studies proved the diagnosis of myxoid variant of Malignant Fibrous Histiocytoma. Therefore radiotherapy and chemotherapy was started for the patient but six months later the symptoms returned and CT scan showed a right maxillary and ethmoidal mass that extended to base of the skull. Maxillectomy and ethmoidectomy were performed for the patient, but 2 months later he died because of the extension of the tumor, which confirmed the necessity of early diagnosis. Conclusion: Amplified radical surgery is the first choice of treatment. The second surgery has special value to the recurrent patients. Radiotherapy alone or chemotherapy alone is not effective to MFH of head and neck region